(untitled) (International Journal of Nursing Education, 2020)
Introduction: Junior nursing students who are enrolled in the psychiatric and mental health practicum mayfeel anxious and stressed due to a lack of self-preparation before taking part in the clinical work. Such feelingscan have an influence on self-confidence, which, in turn, can affect achievement of learning outcomes (LOs)and knowledge. Team-based Learning (TBL) is one of the useful techniques that clinical instructors canapply to promote junior nursing students’ self-confidence, thus increasing both their knowledge and LOs.Aims: To compare the pre-test and post-test scores of knowledge and self-confidence to achieve LOs ofjunior nursing students in both the experimental and control groups.Materials and Method: This quasi-experimental study employed a two-group pre-test and post-test design.The conceptual framework was developed based on an integration of the framework proposed by Michaelsenet al. (2004) and the Thai qualification framework (TQF). The sample consisted of junior nursing studentsrecruited by means of purposive sampling, with 32 in the experimental group receiving TBL in the orientationclass and 32 in the control group who had only self-preparation. Students’ knowledge questionnaire, selfconfidence for achieving learning outcomes questionnaire, and demographic data questionnaire were usedto collect the data.Results: There were statistically significant differences in both the scores of knowledge and self-confident toachieve learning outcomes of the experimental group received TBL (p < .001) and the control group.Conclusion: TBL can be used to enable nursing students to achieve learning outcomes in the psychiatric andmental health nursing field.